La Loire, espace d’une gouvernance environnementale ? - Franck Huyghues Despointes (VertigO, 2009)
This work analyses the Loire river policy over a thirty year period. This policy was at first meant to be a politically-driven project to spatially and economically regenerate a particular area but became later a transversal public policy whereby the environment, and then the notion of heritage, became key factors. The Loire river was approached from both a spatial perspective as well as a temporal one. Within this thesis it was necessary to reconstruct the decision making process over time in order to understand where we started from and where we are today. The Loire river public policy is a mixture of diverse purposes : regeneration of a hydrosystem, ecology, urban regeneration, landscape, the notion of heritage and the notion of world heritage. The Loire river has been a platform upon which many projects have been developed, but rarely leading to concrete results. The few results achieved are truly complex. The Loire river has been a place around which many debates, conflicts of ideology, and action have occurred. The objective is to understand the Loire river related public policy as well as its evolution. This was done from the perspective of the changes introduced by the involvement of “territorial agents” i.e. some local public actors, as well as some ecology-driven ones. The latter took part in the gradual reshaping the public policy objectives of the area under scrutiny. We also wanted to address the hypothesis according to which territorial governance was to be put in place. This territorial governance was to symbolize the renewal of the public policy. We wish to see if, as is often said, the sort of actions and relations between different agents involved in the Loire projects have had an impact on public policies of other geographical sites and areas.